Work–Life Balance, Leadership, Organizational Commitment, and Employee Performance - Christina Vania Sabrina; Joko Suyono; Damarsari Ratnasahara Elisabeth; Mochamad Fathurrohman (LPPM of NAROTAMA UNIVERSITY, 2026)
Purpose: This study aims to examine the influence of work–life balance, leadership and organizational commitment on employee performance. Specifically, it investigates the partial and simultaneous influence of. Design/methodology/approach: A quantitative research design was employed using a survey approach. The study involved all 57 employees of the Genteng District Office, Surabaya, selected through a total sampling technique. Data were analyzed using multiple linear regression to examine both the partial and simultaneous influence of work–life balance, leadership, and organizational commitment on employee performance. Findings: The findings reveal that work–life balance, leadership, and organizational commitment each have a positive and significant influence on employee performance. Simultaneously, the three independent variables significantly influence employee performance. Research limitations/implications: This study is limited to employees of a single public-sector institution. Practical implications: The findings suggest that public organizations should strengthen organizational commitment while promoting effective leadership practices and supporting employees' work–life balance. These efforts can contribute to improving employee performance and overall organizational effectiveness. Originality/value: This study contributes to the human resource management literature by providing empirical evidence on the combined effects of work–life balance, leadership, and organizational commitment on employee performance in the Indonesian public sector. Paper type: Research paper (quantitative study)